Dietary reconstruction of the El Sidrón Neandertal familial group (Spain) in the context of other Neandertal and modern hunter-gatherer groups. A molar microwear texture analysis. Issue 104 (March 2017) - Estalrrich, Almudena; El Zaatari, Sireen; Rosas, Antonio
Abstract: Here, we present the analysis of occlusal molar microwear textures of eight individuals from the El Sidrón Neandertal group (Spain). The aims of the study were: 1) to document potential age-, sex-, and maternal lineage-related differences in diet within a Neandertal familial group, and 2) to place the diet of El Sidrón individuals in the context of those of other Neandertal groups. This study also offers an interpretation of the diet of the El Sidrón Neandertals by comparing their microwear signatures to those of recent hunter-gatherer populations with diverse but known diets. The intra-group examination of the microwear signatures are consistent with the females of the El Sidrón group having had more abrasive diets or having used their teeth in more para-masticatory activities than did the males. Aside from the potential sex-related differences in diet, no additional intra-group dietary separation, such as by age group or maternal lineage, was observed. In comparison to other Neandertals, El Sidrón individuals, as a group, have microwear signatures most similar to those of other Neandertals from wooded habitats and different from those that lived in more open habitats. This result is expected based on the available paleoenvironmental reconstructions from El Sidrón Cave. The diet of the El Sidrón Neandertals, just like their Neandertal counterparts from similar wooded habitats, is interpreted as having been mixed, consisting of both meat and vegetable foods.